Megacolon agangliónico. Técnica quirúrgica original. - González -Rodiles Planas, Juan; Mendibur Morodo, Avelino; González, Ricardo; Rodríguez Cárdenas, Javier; Valdés Mena, Ambrosia (Revista Cubana de Pediatría, 2023)
Búsqueda de una nueva técnica quirúrgica.